PENGARUH ASAM FORMIAT PADA BULU AYAM SEBAGAI ADSORBEN TERHADAP PENURUNAN KADAR LARUTAN ZAT WARNA TEKSTIL REMAZOL GOLDEN YELLOW RNL - Sa'adah, Nailys (Chem Info Journal, 2013)
Effect of Formic Acid to Hen Feathers As Adsorbent for Decreasing Concentration Levels of Remazol Golden Yellow RNL Textile Dye. Hen feathers is a waste that can be utilized because of the content of keratin existence. keratin is fiber protein containing amino acids such as cysteine. Research which is trying to modify a hen feathers by the addition of formic acid in adsorption method to decrease the levels of textile dye solution until now has not been reported. This study began by preparing the feather as adsorbent and then followed by treatment using formic acid for hen feathers. Results showed that feather adsorbent without and with formic acid treatment produced the different level of dye decrease. This is because the addition of formic acid can enlarge the pores of the hen feathers so that the resulting the more effective adsorption, indicated by the 66.09% increase in surface area, 29.22% increase in pore average and 114.93% % increase in total pore volume. While the value of the maximum adsorption capacity of untreated feathers and with formic acid treatment amounted to 7.892 mg/g and 10.471 mg/g.